Determination of the general toxicity of the enriching compositions of bakeries using Stylonychia mytilus cultures - E. V. Belokurova; M. A. Sargsyan; N. A. Galochkina; N. M. Derkanosova (Новые технологии, 2024)
In order to improve public health, it is necessary to adhere to the basic principles of a healthy lifestyle, which include maintaining physical activity, a balanced diet, giving up tobacco and alcohol consumption, as well as a number of other measures aimed at improving the quality and extending life expectancy. In particular, a regular imbalance of consumed vital nutrients contributes to the development of diseases such as vitamin deficiency and microelementosis. The most common causes of microelementosis include the quality of drinking water, the impact of anthropogenic factors on the environment and population, soil characteristics in the food production region, and others. One of the mechanisms for regulating violations of the elemental status of the population in regions with a recorded imbalance of essential elements is diet correction, which also includes the use of fortified food products. In order to optimize the technology for the production of functional products within small food enterprises and ensure the development of the market for functional bakery products, it is advisable to search for new methods for enriching basic food products with vital microelements. The purpose of the research was to assess the general toxicity of the formed enriching composition based on chitosan and zinc. To achieve this, an express method to determine the general toxicity on ciliates of the Stylonychia mytilus genus was used. The research allows us to conclude that it is safe to use a composition of chitosan and zinc in the recipes of bread made from premium wheat flour and whole grain wheat flour. The results are aimed at optimizing the technology of bread fortification by immobilizing the necessary essential microelement on the surface of a biopolymer carrier.